2005
DOI: 10.1111/j.1365-2257.2005.00673.x
|View full text |Cite
|
Sign up to set email alerts
|

Blood lead levels in iron-deficient and noniron-deficient adults

Abstract: Iron deficiency (ID) has been reported to increase lead absorption. This relationship has been investigated in detail in children but not in adults. This study was designed to investigate whether blood lead levels are significantly higher in iron-deficient adults. ID-parameters (haemoglobin, mean corpuscular volume, mean corpuscular haemoglobin, serum iron, total iron-binding capacity, iron-binding saturation, soluble transferrin receptors, washed zinc protoporphyrin and ferritin) together with whole blood lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 16 publications
1
11
0
1
Order By: Relevance
“…The present study revealed that there is no association between Fe and blood lead levels, which is concordant with previous data [31–34]. However, Kim et al [35] reported a decrease in the serum Fe level in lead-exposed workers, but a significantly lower dietary Fe intake was observed concurrently.…”
Section: Discussionsupporting
confidence: 92%
“…The present study revealed that there is no association between Fe and blood lead levels, which is concordant with previous data [31–34]. However, Kim et al [35] reported a decrease in the serum Fe level in lead-exposed workers, but a significantly lower dietary Fe intake was observed concurrently.…”
Section: Discussionsupporting
confidence: 92%
“…Many studies especially in paediatric group have revealed that ID and/ or IDA can elevate blood lead concentration with increase blood lead absorption in gastrointestinal tract 34911222425. There is a hypothesis for this increase in lead absorption.…”
Section: Discussionmentioning
confidence: 99%
“…Children especially infants are at high risk for ID because of high demand for iron and low diet iron during a period of rapid growth. Both ID and lead poisoning are harmful for early development and growth in children and may cause profound neurologic and developmental effects such as cognitive and behaviour problems 345. During 1976-1980, blood lead concentration was more than 10 μg/dl in 78% of people in the United state, but it was reduced to 20% in 1998 3.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations